1998
DOI: 10.1038/sj.ijo.0800605
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure and physical fitness in overweight vs non-overweight prepubertal girls

Abstract: OBJECTIVE: To determine whether overweight children have lower physical activity energy expenditure (EE) and ®tness levels than non-overweight children. STUDY DESIGN: Twenty-four healthy girls aged 7±10 y were divided into overweight ( b 95th percentile weight-forheight) and non-overweight (10±90th percentile) groups. Basal metabolic rate (BMR), sleeping metabolic rate (SMR), 24 h sedentary EE (SEE) and total EE (TEE) were measured by room respiration calorimetry and doubly labelled water. Physical activity EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 27 publications
7
71
0
2
Order By: Relevance
“…31 A more recent longitudinal observational study reported larger 1 y increases in BMI in association with lower self-reported physical activity levels in 9 -14-y-old children, 32 and other observational studies have reported an inverse association of body weight, percentage body fat or fat mass with physical activity in children. 33,34 A new finding in the present study was the association of fat-free mass with physical activity only in children with below median systolic blood pressure or percentage body fat. Interpretation of this finding is challenging, because, in addition to higher relative and absolute fat mass, obese children also have higher fat-free mass than lean children.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…31 A more recent longitudinal observational study reported larger 1 y increases in BMI in association with lower self-reported physical activity levels in 9 -14-y-old children, 32 and other observational studies have reported an inverse association of body weight, percentage body fat or fat mass with physical activity in children. 33,34 A new finding in the present study was the association of fat-free mass with physical activity only in children with below median systolic blood pressure or percentage body fat. Interpretation of this finding is challenging, because, in addition to higher relative and absolute fat mass, obese children also have higher fat-free mass than lean children.…”
Section: Discussionmentioning
confidence: 47%
“…Interpretation of this finding is challenging, because, in addition to higher relative and absolute fat mass, obese children also have higher fat-free mass than lean children. 33,34 We speculate that in relatively lean children the effect of physical activity is concentrated on increasing fat-free mass development, rather than further reducing an already appropriate relative amount of body fat.…”
Section: Discussionmentioning
confidence: 94%
“…Any impact of body weight on PAL would be expected to be subtler than that of the observed METs, however, because TEE is a composite of the energy expenditure of activities that are influenced by body weight and those that are not. An influence of body weight on PAL might explain the observation of similar PAL values between obese and nonobese children, [19][20][21] while activity diaries document obese children spending more time in sedentary activity and less time in nonsedentary activity compared with nonobese children. 20 The similar PAL values may be a function of obese children spending less time than their nonobese peers in physical activity, yet at a greater energy cost.…”
Section: Discussionmentioning
confidence: 98%
“…8 Previous research on physical activity in paediatric obesity has focused on non-clinical samples, comparing habitual physical activity or energy expenditure in obese and nonobese children and adolescents. [9][10][11][12][13][14][15][16] Most of these studies found lower levels of physical activity and *PAL (TEE/REE) in obese children and adolescents relative to their lean counterparts. [9][10][11][12][14][15][16] The few studies that have compared objec-tively measured sedentary behaviour in non-clinical samples of obese and lean children have reported inconsistent results.…”
Section: Introductionmentioning
confidence: 99%